Implementation Of Subuh Ceria as an Effort to Increase Students' Learning Motivation - Faqih Khodir; Hosna Rofiatul; Nina Zulva Syaatin (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This research wants to obtain information regarding the Cheerful Dawn program in increasing santris' learning motivation at the Al-Ihsan Kalijaring Jombang Islamic Boarding School. For the Islamic boarding school, researcher hope that this research can provide new knowledge and insight as a reference and reflection in increasing students' learning motivation. This research uses a qualitative descriptive method that focuses on a particular incident to describe and explain a social phenomenon. In the data collection process, the researcher applied interview methods, documentation, and observation methods. The results of the research show that the application or implementation of Cheerful Dawn at the Al Ihsan Islamic Boarding School Kalijaring Jombang had gone according to plan. Supporting factors for the implementation of the Cheerful Dawn program so that it can increase santris' learning motivation were the motivation of caregivers, administrators, and assistants as well as adequate facilities and infrastructure. The inhibiting factors include; (1) The santris, activity schedule was busy or at the same time as the Islamic boarding school's activities so some santris’ woke up early in the morning not according to the schedule determined by the Islamic boarding school administrators (2). Feeling tired Good from an administrator or from impactful santris not enough maximum in implementing a cheerful dawn program and (3) queuing for bathrooms and ablution places.